“Survey – interview”. A instrument to characterize a population of weavers: an experience from the design - Fernández Samacá, Martha (Universidad Católica de Pereira, 2017)
The paper introduces from the discipline of design, the theoretical argument for designing an instrument called ‘survey-interview,’ which was used to characterize the population of artisan weavers of the municipalities of Duitama and Sogamoso, Colombia, who were certified in labor skills, from 2009 to 2012, by the National Learning Service SENA. This government entity along with the Craft Sector Board measures the impact of the competency certification process on the artisans’ competitiveness. Moreover, the article presents the contextualization of assessment in the certification process, the historical context of the weaving in Boyaca province, Colombia, and questions used for the characterization of the population.